A Systematic Review: The Experience of Patient with Diabetic Foot Ulcers - Mohamad Roni Alfaqih; Kusnanto Kusnanto; Padoli Padoli (Universitas Airlangga, 2020)
Introduction: Diabetic foot ulcers can have an impact on the individual responses related to the disease process and healing. The response depends on the perception of the disease, its severity, the environmental factors and the level of family support. The response that often occurs is the existence of fear and anxiety which is due to the stress experienced by the individual. The purpose of this study was to explore the experience of patients with diabetic foot ulcers.Methods: This study used the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) approach. The methods used to arrange this systematic review included (1) the identification of the variables in the literature, (2) the identification of the relevant literature based on the topic and title, (3) obtaining the literature in full-text form and (4) conducting an analysis of the results from the literature. The databases used to identify suitable articles were Scopus, Google Scholar, Pubmed, ProQuest and Ebscohost.Results: Based on the 15 articles reviewed, the results explains that the majority of patients who experience DM with the complication of diabetic ulcers experience stress, depression and anxiety. They also have a financial burden, feel helplessness, blame themselves and feel that there is uncertainty their life. They need support from their family and wider social support.Conclusion: However, from the experience of the patients with diabetic foot ulcers, they must be able to adapt to a limited life. They must also have a good coping style and an adaptive response in order to survive and heal their diabetic ulcers.